The Feasibility of Music and Talk Radio Program as a Focus Stimulant for Driver - Aminuddin, M.M.M.; Nasir, H.M. (International Journal of Human and Technology Interaction (IJHaTI), 2018)
Long distance driver tends to listen to the music in order to help them awake on the road. However, several studies have reported that music has repetition element which is a catalyst to attention deficit phenomenon. This study evaluated the feasibility of music and talk radio program as a stimulant to keep our focus behind the wheel. N1 waves of 11 participants were studied and the results have suggested that music is not a good stimulant for driving partner compared to talk radio program. All the participants showed a great attention when listened to talk program compared to music of their choice.